Peran Sekolah Dalam Penguatan Sikap Sopan Santun Melalui Pembiasaan 5S (Senyum, Salam, Sapa, Sopan, dan Santun) Siswa Kelas X Kuliner 5 di SMKN 2 Boyolangu - Merisa Eka Purnamasari; Winarsih; Ahmad Izzul Ito’ (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Strengthening politeness through the 5S habituation (smile, greeting, greeting, politeness, and courtesy) has not been consistently implemented by all students so that polite behavior in the school environment still varies. This study aims to analyze the role of schools in strengthening politeness through the 5S habituation and identify supporting and inhibiting factors in its implementation in class X Culinary 5 students at SMKN 2 Boyolangu. This study uses a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving the vice principal of student affairs, homeroom teachers, guidance counselors, subject teachers, and students. Data analysis techniques were carried out through the stages of data reduction, data presentation, and drawing conclusions, with the validity of the data tested through triangulation of sources and techniques. The results of the study indicate that schools play a role in strengthening politeness through the implementation of the 5S program, teacher role models, character building, implementation of rules, and providing reinforcement. Supporting factors include school policies, teacher role models, discipline, and the involvement of the school community, while inhibiting factors include low awareness among some students, lack of familiarization within the family environment, peer influence, and social media. It was concluded that consistently implementing 5S habits is effective in strengthening students' politeness